Exosomal microRNA Therapy for Non-Small-Cell Lung Cancer - Chen, Jibing; Wu, Fasheng; Hou, Encun; Zeng, Jianying; Li, Fujun; Gao, Hongjun (Technology in cancer research & treatment, 2023)
With the progress of molecular diagnosis research on non-small cell lung cancer (NSCLC) cells, four identified categories of microRNAs have been found to be related to disease diagnosis, diagnosis of treatment resistance, prediction of prognosis, and drugs for treatment. To date, nine target mRNA/signal pathways have been confirmed for microRNA drug therapy both in vitro and in vivo. When microRNA drugs enter blood vessels, they target the tumor site and play a similar role to that of targeted drugs. However, whether they will produce serious off-target effects remains unknown, and further clinical research is needed. This review provides the first summary of microRNA therapy for NSCLC.